Neuropsychological outcome of patients operated upon for an intracranial aneurysm: analysis of general prognostic factors and of the effects of the location of the aneurysm. Issue 10 (October 1989) - Desantis, A; Laiacona, M; Barbarotto, R; Basso, A; Villani, R; Spagnoli, D; Capitani, E
Abstract : One hundred and fourteen patients operated on for an intracranial aneurysm were followed up in order to investigate their neuropsychological outcome and to detect if there were any clinical features assessed around the time of operation that had prognostic significance. The neuropsychological examination evaluated language, apraxia, memory, intelligence and spatial ability. In the statistical analysis the overall severity of neuropsychological disorder was studied. "Late surgery timing" had a negative influence upon the neuropsychological outcome. There was not a difference between different aneurysm sites. Several patients with an apparently good clinical outcome showed neuropsychological deficits. Neuropsychological assessment is important in the evaluation of outcome after subarachnoid haemorrhage.